Perancangan Aplikasi Pemantau Keamanan Berdasarkan Pergerakan Menggunakan Koneksi Email, Handphone dan Video - Dian Hartanti (Sekolah Tinggi Teknik - PLN, 2015)
It is natural that every human being wants guaranteed security of themselves and the surrounding environment , due to its higher level of crime that occurs not only outside, but also inside the home . So the emergence of thought to create an application that can look around without having to be monitored within a close eye , the user can view the site conditions are monitored from a far distance area by utilizing information technology program uses a familiar interface and easy to use . Its main utilization is used for security systems , with the output data in the form of video , can be monitored from a long distance utilizing the mobile communication device that the camera captures a webcam and sent via e - mail to the user .